Metabolism of versicolorin A, a genotoxic precursor of aflatoxin B1: Characterization of metabolites using in vitro production of standards. (September 2022) - Al-Ayoubi, Carine; Oules, Justin; Person, Elodie; Bruel, Sandrine; Bouville, Alyssa; Pinton, Philippe; Oswald, Isabelle P.; Jamin, Emilien L.; Puel, Olivier; Soler, Laura
Abstract: The toxicity of mycotoxins containing bisfuranoid structures such as aflatoxin B1 (AFB1) depends largely on biotransformation processes. While the genotoxicity and mutagenicity of several bisfuranoid mycotoxins including AFB1 and sterigmatocystin have been linked to in vivo bioactivation of these molecules into reactive epoxide forms, the metabolites of genotoxic and mutagenic AFB1 precursor versicolorin A (VerA) have not yet been characterized. Because this molecule is not available commercially, our strategy was to produce a library of metabolites derived from the biotransformation of in-house purified VerA, following incubation with human liver S9 fractions, in presence of appropriate cofactors. The resulting chromatographic and mass-spectrometric data were used to identify VerA metabolites produced by intestinal cell lines as well as intestinal and liver tissues exposed ex vivo . In this way, we obtained a panel of metabolites suggesting the involvement of phase I (M + O) and phase II (glucuronide and sulfate metabolites) enzymes, the latter of which is implicated in the detoxification process. This first qualitative description of the metabolization products of VerA suggests bioactivation of the molecule into an epoxide form and provides qualitative analytic data to further conduct a precise metabolism study of VerA required for the risk assessment of this emerging mycotoxin. Graphical abstract: Image 1 Highlights: Metabolites characterization of versicolorin A. In vitro production of reference materials to produce analytical data using S9 fractions. Tandem mass spectrometry data of metabolites of versicolorine A. Identification of ex vivo produced metabolites of versicolorine A, thanks to reference data obtained with S9 fractions. Qualitative description of detoxification and bioactivation products of versicolorin A.